MERIAM KARBIT DAN ROBO’-ROBO’: PELESTARIAN TRADISI IKONIS MELAYU KALIMANTAN BARAT DALAM PENCAPAIAN MAQASHID SYARI’AH - Noviansyah, Noviansyah; Yanti, Mauliani Harva; Damero, Lian; Heriyanto, Heriyanto (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The purpose of this article is to examine the iconic traditions of Malay Pontianak, namely the carbide cannon and robo'-robo', in achieving the maqasid al-Shari'ah (objectives of Islamic law). This article is an empirical legal research with a maqasid al-Shari'ah approach. The method used is descriptive qualitative. The research results show that the iconic traditions of Malay Pontianak are in accordance with the principles of maqasid al-Shari'ah. This fact is evidenced by the preservation of five main aspects of human life, including the growth of religious values that provide steadfastness in faith towards Allah SWT (hifdz al-din), the development of a characterful soul, physical and spiritual health (hifdz al-nafs), contributing to the development of new knowledge through positive analytical thinking (hifdz al-aql), contributing to a sense of gratitude and a good understanding of wealth management (hifdz al-mal), and preserving the culture and social environment to achieve a peaceful way of life (hifdz al-nasbi).